Pengaruh Harga, Iklan dan Citra Merek Terhadap Keputusan Pembelian Air Minum Dalam Kemasan Pada PT. Lingkoq Pandan Narmada - Erviva Farianti; Hengki Samudra (Fakultas Ekonomi Universitas Islam Al-Azhar, 2020)
This study aims to determine how much influence the price, advertising and brand image of the decision to purchase bottled water at PT Lingkoq Pandan Narmada. And this study also aims to analyze the most dominant factor influencing the purchase decision of bottled water at PT Lingkoq Pandan Narmada. The population used in this study were all bottled drinking water consumers at PT Lingkoq Pandan Narmada whose numbers are not known with certainty. The sample in this study were 50 respondents and the analysis technique used was multiple linear regression analysis with a sampling technique using an incidental approach (the technique of determining samples based on chance). From this analysis obtained the regression equation as follows: Y = 1,274 + 0.511X1 + 0.217X2 + 0.5 02X3 + 1.544. Price variable (X1 ) has the most dominant influence on purchasing decisions of 0.511 , then followed by brand image variable (X3 ) of 0.502 and advertising variable (X2) has the lowest effect of 0.217 . Hypothesis testing using the T test showed that the three independent variables consisting of price (X1), advertising (X2) and brand image (X3) which were examined were proven to be positive and significantly affected the dependent variable, namely the purchasing decision (Y). Then through the F test it can be seen that the price variable (X1) , advertising (X2) and brand image (X3) are indeed feasible to test the dependent variable namely the purchasing decision (Y) . Figures Adjusted R Square shows that 78.4 % variation in purchasing decisions can be explained by the three independent variables in the multiple regression equation. While s elisih its 21.6 % influenced by other variables that are not researched in this study .